PENGARUH PENGETAHUAN PERPAJAKAN, SELF ASSESMENT SYSTEM, E-FILING DAN SANKSI PAJAK TERHADAP MOTIVASI WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Yogyakarta) - Teguh Erawati; Gloria Maindo Mau Pelu (Fakultas Ekonomi UNIBBA, 2021)
This study aims to test whether knowledge of taxation, self-assessment, e-filing and tax sanctions affect the motivation of individual taxpayers in paying taxes. This research method uses quantitative methods and questionnaire primary data. This study took samples from individual taxpayers registered at KPP Pratama Yogyakarta. Data processing was tested by classical assumption test and hypothesis testing with normality test, Multicollinearity test, Heteroscedasticity test, t test, F test, Multiple Linear Regression and R2 test. The sampling technique uses probability sampling by using the incidental sampling method. Data collection is done by distributing questionnaires offline and online by distributing questionnaire links in the form of a google form. The number of questionnaires that were processed were 100 questionnaires. The results of this study indicate that knowledge of taxation, self-assessment system, e-filing and tax sanctions have a positive effect on the motivation of individual taxpayers in paying taxes